Performance Evaluation of Mutual Funds in Indonesia: An Analysis of Risk-Adjusted and Market Timing - Teddy Rianto L. Gaol; Nugroho J Setiadi; Arina Azwani; Erwin Febriansyah (Politeknik Ganesha Medan, 2025)
This research investigates the performance of 38 Indonesian mutual funds, consisting of 21 fixed income funds and 17 equity funds, from August 2017 to May 2025. The evaluation employs various risk-adjusted performance measures, including the Sharpe ratio and Jensen’s alpha, as well as market timing analysis using the Treynor-Mazuy and Henriksson-Merton models. The results indicate that fixed income funds posted a higher average monthly return (0.34%) than both equity funds (0.08%) and the market index (0.30%). Notably, the risk-free rate (0.45%) surpassed the returns of all fund categories and the market. Performance analysis reveals that only 10 funds outperformed the market based on the Sharpe ratio, and just one fund recorded a statistically significant positive Jensen’s alpha. Similarly, market timing evaluation identified only one fund with a significant positive coefficient, suggesting effective market timing ability. These findings are consistent with the Efficient Market Hypothesis, implying that most Indonesian mutual funds are unable to consistently generate superior risk-adjusted returns or exhibit strong market timing skills. The study provides relevant insights for investors and fund managers regarding mutual fund selection and performance expectations in Indonesia. However, the research acknowledges limitations in sample size and scope, recommending that future studies include broader samples, longer observation periods, and additional explanatory variables to enrich the understanding of mutual fund performance in the Indonesian capital market.